Philosophy of Santri Alms as a Form of Response to Socio-Spiritual Gaps: Phenomenological Studies on the Concept of Altruism - Sri Wahyuni, Sandiani; Zahro Nur Latifah; Kartika Anggraeni Sudiono Putri (CV. Ulil Albab Corp, 2024)
This study investigates the philosophy of